2006
DOI: 10.1038/sj.eye.6702307
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure control in type II diabetics with diabetic retinopathy

Abstract: Background Large clinical trials have emphasized that blood pressure control provides a major clinical benefit in reducing the risk of blindness in patients with diabetic retinopathy. Methods This audit was carried out to assess the quality of care for hypertension in 100 consecutive type II diabetics with diabetic retinopathy.Results The target blood pressure of 140/ 80 mmHg was achieved only in 38% of the patients. We also observed that 65% of the patients requiring diabetic macular laser treatment in this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…The combination of diabetes and hypertension is a particularly strong cardiovascular risk factor and blood pressure control is often suboptimal in patients with diabetes [3,4]. Blocking the renin-angiotensinaldosterone system (RAAS) has obviously been a very successful therapeutic strategy in both heart failure and diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of diabetes and hypertension is a particularly strong cardiovascular risk factor and blood pressure control is often suboptimal in patients with diabetes [3,4]. Blocking the renin-angiotensinaldosterone system (RAAS) has obviously been a very successful therapeutic strategy in both heart failure and diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…The UKPDS found that tight control of blood pressure led to a 34% reduction in the rate of progression of retinopathy; more specifically, this trial found that for each 10 mmHg decrease in systolic blood pressure there was a 13% reduction in the risk of retinopathy [3, 5]. The UKPDS also showed that in patients with T2D, systolic blood pressure was strongly linked to the incidence of diabetic retinopathy [24].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that blood pressure, a very easily measured parameter, may be a strong determining factor in identifying patients who would benefit from referral to the diabetologist. One study has suggested that blood pressure should be measured in all patients at every diabetes clinic appointment with the ophthalmologist [5]. However, in another study blood pressure recordings at an eye clinic were found to be significantly higher than comparative diabetes clinic measurements, possibly secondary to the white-coat effect [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[51520] Approximately 60% of adults with Type 2 diabetes have comorbid hypertension. [21] A follow-up study of hypertensive diabetics showed that tight control of hypertension decreased the risk of diabetic complications compared to less aggressive control. [1622]…”
Section: Discussionmentioning
confidence: 99%